EXTENT OF ACQUISITION OF DIGITAL SKILLS BY OFFICE TECHNOLOGY AND MANAGEMENT STUDENTS IN TERTIARY INSTITUTIONS IN BENUE STATE (NAU Journal of Technology and Vocational Education, 2024)
This study investigated the extent of acquisition of digital skills by Office Technology andManagement (OTM) students in tertiary institutions in Benue State. Two research questionsguided the study and two null hypotheses were tested. Survey research design was used. Thepopulation of the study was 515 office technology students drawn from four tertiary institutionsin Benue State. Simple random sampling was used to get a sample size of 51 students for thestudy. Instrument used for data collection was a 5- point rating scale structured questionnaire.Data collected were analyzed using mean and standard deviation to answer the researchquestions while t-test and ANOVA were used to test the hypotheses at 0.05 level of significance.The overall result showed that the acquisition of these digital skills by OTM students in tertiaryinstitutions in Benue State was at a moderate extent. The result of the hypotheses test showedthat there was no significant difference in the mean ratings of OTM students in universities,polytechnics and colleges of education on the extent of acquisition of skills in the two digitalapplications. Similiary, gender was significant. It was concluded that, OTM students in tertiaryinstitutions in Benue State did not have enough of the two digital skills applications to meet thechallenges of competitive nature of office work today. It was recommended that tertiaryinstitutions should try to provide adequate digital facilities for better training of students toenhance mastery of the needed skills upon graduation.
Keywords: Digital Skills, Office, Students, Tertiary Institutions and Gender